Effect of Budget Defict on Private Investment in East African Community for the Period 1981-2015: A Panel Data Analysis - Mose, Naftaly Gisore; Keino, Irene Jepchumba (International Journal of Business, Economics and Management, 2017)
Over the period of thirty four years, between 1981 and 2015, the East African Community economies have witnessed inconsistent and downward trend on the level of private investments as percentage of GDP. Several studies have been done regarding the determinants of private investment at country level while others have focused on budget/fiscal deficit, regional integration and economic growth but the findings are inconsistent. However, from the empirical literature review, most of the studies ignore effect of budget deficit on private investment. It is against this background that this study was carried out to investigate the effect of budget deficit on private investment in EAC using panel data over the period 1981-2015. The study adopted the Modified Flexible Accelerator model. Using Levin et al. (2002) to test the unit root, the study found the variable to be non-stationary at level. Co-integration test error correction model were carried to analyze the long-term and short-term dynamic of the selected macroeconomic variables on budget deficit account. The study results showed that fiscal deficit had a negative effect on private investment in the region. Debt reduction and government expenditure scaling down strategies should also be adopted in the region so as to improve the fiscal deficit hence boosting private investment and faster real GDP growth in the long run.